Partisipasi Masyarakat dalam Mewujudkan Pelayanan Publik Berkualitas di Kabupaten Labuhanbatu - Sefri Doni; Rita Purnama Sari; Siti Masliyah Lubis (Jurnal Pembangunan Nagari, 2023)
This research is intended to reveal the existing condition of public services and the level of community participation in public services in Labuhanbatu Regency with the following objectives: 1) to find out the existing condition of the compliance level of the Local Government of Labuhanbatu Regency to public service standards, 2) to find out the level of community participation in public services in Labuhan Batu District. This research was conducted at 8 locations, namely the Population and Civil Registration Service, Investment Service and One Stop Services, Social Service, Sigambal Health Center, Negeri Lama Health Center, Education Office, Manpower Office and Library and Archives Service. The method used is qualitative with data collection techniques by interviews, observation and document review. The results of the study show that the current condition of public services in Labuhanbatu Regency still has many shortcomings when viewed from the minimum standards as mandated by Law Number 20 of 2009 concerning Public Services. Not only that, community participation is also still very low in planning, monitoring and evaluating the implementation of public services in Labuhanbatu Regency. Thus the Regional Government of Labuhanbatu Regency needs to improve overall guidance, supervision and evaluation of the implementation of public service delivery in Labuhanbatu Regency.